Architectuur in Nederland : Jaarboek 2016/17 - Hannema, Kirsten, ....-; de Kort, Robert-Jan, 1979-; Schrijver, Lara, 1971- (Rotterdam : nai010 uitgevers, 2017)
Architecture in the Netherlands' has been an indispensable reference work for anyone interested or professionally involved in Dutch architecture for 30 years. The Yearbook is Dutch architecture?s international calling card. The three-person editorial team selects noteworthy projects that were completed in the past year and describes major developments that affect Dutch architecture, with particular attention to commissionership, architecture policy and projects that have achieved spectacular results with limited resources. With a special contribution by Oliver Wainwright (architecture and design critic of 'The Guardian') on Dutch architecture as an export product.
Texts in Dutch and in English
Keywords: Architecture -- 21st century -- Netherlands